Where Are the Fathers? The Effects of Earmarking Parental Leave on Fathers in France - Hélène Périvier; Gregory Verdugo (Institute of Labor Economics (IZA), 2023)
Does providing nontransferable months of parental leave earmarked to fathers, as mandated by the European Union to its member countries since 2019, increase their participation? To answer that question, the authors investigate the consequences of a 2015 French reform that earmarked up to 12 months of paid leave for fathers while simultaneously reducing the maximum paid leave for mothers by the same number of months. While the benefits were low, parental leave could be taken part-time, which can be more attractive for fathers. Using administrative data and comparing parents of children born before and after the reform, the authors find that in response to a 25 p.p. decline in mothers' participation rate triggered by the reform, fathers' participation increased by less than 1 p.p., mostly through part-time leave. The reform increased mothers' labor earnings, but it had no significant impact on fathers' earnings.
Keywords: J16; D13; J18; 330; gender inequality; labor supply; parental leave